Intensity and duration of salinity required to form adaptive response in C4 halophyte Kochia prostrata (L.) Shrad - Shuyskaya, Elena; Rakhmankulova, Zulfira; Prokofieva, Maria; Saidova, Luizat; Toderich, Kristina; Voronin, Pavel (Frontiers in Plant Science, 2022)
Plant adaptation to salinity is a highly multifaceted process, harnessing various physiological mechanisms depending on the severity and duration of salt stress. This study focuses on the effects of 4- and 10-day treatments with low (100 mM NaCl) and moderate (200 mM NaCl) salinity on growth, CO2/H2O gas exchange, stomatal apparatus performance, the efficiency of photosystems I and II (PS I and II), content of key C4 photosynthesis enzymes, and the accumulation of Na+, K+, and proline in shoots of the widespread forage C4 halophyte Kochia prostrata. Our data show that 4 days of low salinity treatment resulted in a decrease in biomass, intensity of apparent photosynthesis, and cyclic electron transport around PS I. It was accompanied by an increase in transpiration and Rubisco and PEPC contents, while the Na+ and proline contents were low in K. prostrata shoots. By the 10th day of salinity, Na+ and proline have accumulated; PS I function has stabilized, while PS II efficiency has decreased due to the enhanced non-photochemical quenching of chlorophyll fluorescence (NPQ). Thus, under low salinity conditions, Na+ accumulated slowly and the imbalance between light and dark reactions of photosynthesis was observed. These processes might be induced by an early sodium signaling wave that affects cellular pH and ion homeostasis, ultimately disturbing photosynthetic electron transport. Another adaptive reaction more “typical” of salt-tolerant species was observed at 200 mM NaCl treatment. It proceeds in two stages. First, during the first 4 days, dry biomass and apparent photosynthesis decrease, whereas stomata sensitivity and dissipation energy during dark respiration increase. In parallel, an active Na+ accumulation and a decreased K+/Na+ ratio take place. Second, by the 10th day, a fully-fledged adaptive response was formed, when growth and apparent photosynthesis stabilized and stomata closed. Decreased dissipation energy, increased WUE, stabilization of Rubisco and PEPC contents, and decreased proline content testify to the completion of the adaptation and stabilization of the physiological state of plants. The obtained results allowed us to conclude that the formation of a full-fledged salt-tolerant response common for halophytes in K. prostrata occurs by the 10th day of moderate salinity.